Extending the Shelf-Life of Immunoassay-Based Microfluidic Chips through Freeze-Drying Sublimation Techniques - Sangjun Moon (Sensors, 2023)
Point-of-care testing (POCT) platforms utilizing immunoassay-based microfluidic chips offer a robust and specific method for detecting target antibodies, demonstrating a wide range of applications in various medical and research settings. Despite their versatility and specificity, the adoption of these immunoassay chips in POCT has been limited by their short shelf-life in liquid environments, attributed to the degradation of immobilized antibodies. This technical limitation presents a barrier, particularly for resource-limited settings where long-term storage and functionality are critical. To address this challenge, we introduce a novel freeze-dry sublimation process aimed at extending the shelf-life of these microfluidic chips without compromising their functional integrity. This study elaborates on the mechanisms by which freeze-drying preserves the bioactivity of the immobilized antibodies, thereby maintaining the chip’s performance over an extended period. Our findings reveal significant shelf-life extension, making it possible for these POCT platforms to be more widely adopted and practically applied, especially in settings with limited resources. This research paves the way for more accessible, long-lasting, and effective POCT solutions, breaking down previous barriers to adoption and application.